2022
DOI: 10.1021/acscatal.2c02345
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Allylation of Alkanes Enabled by Nickel Catalysis

Abstract: We have developed an allylic alkylation of alkanes by dual photo-HAT/nickel catalysis. In this reaction, radical-type hydrogen-atom-transfer of the alkanes is enabled by decatungstate as a photocatalyst, whereas nickel serves to cleave the C–O bond in the substrates under mild reaction conditions. This co-catalyzed reaction provides a method for direct functionalization of alkanes. Density functional theory calculations show that reductive elimination is the rate-determining step of this reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…The allylic alkylation of alkanes by synergistic photo-HAT/ nickel catalysis was reported by Gong et al, Scheme 29. 53 This process enables direct functionalization of alkanes, opening Scheme 47 Photocatalyzed hydroacylation of terminal alkyne.…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%
“…The allylic alkylation of alkanes by synergistic photo-HAT/ nickel catalysis was reported by Gong et al, Scheme 29. 53 This process enables direct functionalization of alkanes, opening Scheme 47 Photocatalyzed hydroacylation of terminal alkyne.…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%
“…Several research articles highlight the ability of Ni(II) bipyridine (bipy), phenanthroline (phen), and related complexes to perform radical C-E (E = C, F) coupling reactions under reducing or photocatalytic conditions. 34,[43][44][45][46] The recent surge of Ni catalysts to perform stereo-convergent cross-coupling reactions benefits from the ability of the Ni species to generate radical intermediates. Liu and Diao recently studied the mechanism of a classical [Ni(bipy)] complex and found that alkyl radical formation forms via a concerted mechanism (Figure 3B) with the bipy ligand acting as an electron reservoir.…”
Section: Redox Active Ligands For Imparting Base Metal Nobilitymentioning
confidence: 99%
“…These feature easily-synthesized pyridine and phosphine derived ligands, allowing for the direct allylation of alkanes under mild conditions. 46 Hosseini-Sarvari, similarly, presents a semi-heterogeneous photocatalytic system in which TiO2 nanoparticles are coupled with a simple NiCl2•glyme catalyst to perform photocatalytic C-P bond formation between aryl iodides and diarylphosphine oxides. 89 Taking inspiration from photosynthetic processes within nature, organic photocatalysts can be used in place of precious metal photoredox systems.…”
Section: Harnessing the Power Of Dual Catalytic Systems For Effective...mentioning
confidence: 99%
“…Notably, the development of efficient chiral dirhodium catalysts developed by Davies has enabled site-selective and stereoselective alkylation of unactivated alkanes (Scheme A, top). Another widely employed strategy is controllable radical C–H functionalization via a hydrogen atom transfer (HAT) process, which finds extensive use in the functionalization of hydrocarbons . In this context, transition-metal-catalyzed radical relay, chiral Lewis acid catalysis, and organocatalyst-mediated radical coupling have enabled enantioselective transformations of aliphatic C–H bonds (Scheme A, middle and bottom).…”
Section: Introductionmentioning
confidence: 99%